Enzymatic antioxidant system in Fraxinus species and forms with varying susceptibility to black sawfly (Tomostethus nigritus) - Shupranova, L.; Holoborodko, K.; Ivanko, I.; Zhukov, O.; Loza, I.; Kabar, A.; Sytnyk, S.; Lovynska, V.; Pakhomov, O.; Gritsan, Y. (Regulatory Mechanisms in Biosystems, 2026)
Degradation of European ash ( Fraxinus excelsior ) stands under the action of biotic stresses requires compensation for the loss of ash trees by searching for alternative local and introduced tree species. There is insufficient study on biochem i cal defense responses in the leaves of ash species and forms with various vulnerability to the damage caused by ash sawfly ( Tomostethus nigritus F.). Our hypothesis is that there are differences in the resistance level of different ash tree sp e cies/forms to T. nigritus based on the study of their antioxidant enzyme system (AOS) activity and soluble protein (SP) content. The measurements of enzyme activity were carried out by spectrophotometric methods. Isoenzyme composition of benzidine peroxidase ( BPx ) was determined by isoelectric focusing. B ased on visual observation, significant differences in susceptibility to black sawfly were found between three ash species and three ornamental forms of F. excelsior , the leaves of which were used for biochemical analyses. The results demonstrated a wide range of interspeci fic activity of enzymes and proteins, which indicates their involvement in plant adaptation to biotic stress. It has been shown that the high level of guaiacol-peroxidase (GPx) and catalase (CAT) activity in the leaves of ornamental forms may be related to their resistance to T. nigritus . The highest level of GPx activity and protein content in the Asian species F. sogdiana co m pared to other ash trees also indicates their important role and can give it benefits in protection against the leaf-chewing pest. Species-specificity of isoelectrofocusing (IEF) profiles of acidic isoperoxidases of BPx was recorded. The molecular forms of BPx with the highest level of activity in the species unaffected by T. nigritus were revealed. The highest inhibit o ry effect of the oligophage black sawfly on the antioxidant system and proteins was observed in the North American sp e cies F. velutina , which should be introduced with caution into urban green areas.